2003
DOI: 10.1016/s0196-8858(02)00528-6
|View full text |Cite
|
Sign up to set email alerts
|

Non-P-recursiveness of numbers of matchings or linear chord diagrams with many crossings

Abstract: In order to prove irrationality of √ 2 by using only decimal expansions (and not fractions), we develop in detail a model of real numbers based on infinite decimals and arithmetic operations with them.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 40 publications
0
23
0
Order By: Relevance
“…If we temporarily forget the parameter z codifying crossings, we know that [Kla03] and proved that it is not D-finite (i.e. the solution of a differential equation with polynomial coefficients).…”
Section: Connected Matchingsmentioning
confidence: 99%
“…If we temporarily forget the parameter z codifying crossings, we know that [Kla03] and proved that it is not D-finite (i.e. the solution of a differential equation with polynomial coefficients).…”
Section: Connected Matchingsmentioning
confidence: 99%
“…The numbers of strongly-irreducible words and strongly-irreducible palindromes have been previously studied within different contexts (see, for example, [17]). In [10] strongly-irreducible palindromes are called ''connected linked diagrams'' and the following formula is obtained. …”
Section: Rigid Vertices All Classes G Nmentioning
confidence: 99%
“…The first few values of the free cumulants of the Gaussian distribution are This sequence of the numbers of irreducible diagrams of 2n nodes has been well-studied from a combinatorial point of view, see, e.g., [41,40]; it appears for example as sequence A000699 in Sloane's Encyclopedia of Integer Sequences [37]. For a recent bibliography of this sequence see [28] where it is shown that the sequence is not holonomic, i.e., it does not satisfy a linear recurrence with polynomial coefficients. However, positivity questions for this sequence have never been considered.…”
Section: Combinatorial Considerationsmentioning
confidence: 99%